2008
DOI: 10.1248/bpb.31.1327
|View full text |Cite
|
Sign up to set email alerts
|

Anti-infectious Effect of S-Benzylisothiourea Compound A22, Which Inhibits the Actin-Like Protein, MreB, in Shigella flexneri

Abstract: Various antibacterial agents have been developed and used for the treatment and prevention of infectious diseases. These drugs show antibacterial activity by inhibiting growth or directly killing bacteria. This antibacterial activity induces the microbial substitution and the emergence of drug-resistant bacteria.1) Therefore, improper use of antibacterial agents selects for drug-resistant bacteria and increases their prevalence. To prevent this problem, it is necessary to develop therapeutic agents that are fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…L. biflexa MreB shares 50 to 60% identity with MreB from E. coli or C. crescentus. To understand the role of MreB, we first used the A22 compound, which has been shown to affect the function and to mimic loss of this actin-like homologue in several Gram-negative microorganisms (5,20,41). Figure 4 shows that cells treated with A22 at concentrations around the MIC level presented a phenotype similar to what we observed when they were subjected to penicillin G. Morphological changes appeared after 8 h. The growth rate was comparable to that of the control cells until 8 h after addition of the compound, and then the cells stopped growing and started lysing 12 h after addition of A22.…”
Section: Resultsmentioning
confidence: 99%
“…L. biflexa MreB shares 50 to 60% identity with MreB from E. coli or C. crescentus. To understand the role of MreB, we first used the A22 compound, which has been shown to affect the function and to mimic loss of this actin-like homologue in several Gram-negative microorganisms (5,20,41). Figure 4 shows that cells treated with A22 at concentrations around the MIC level presented a phenotype similar to what we observed when they were subjected to penicillin G. Morphological changes appeared after 8 h. The growth rate was comparable to that of the control cells until 8 h after addition of the compound, and then the cells stopped growing and started lysing 12 h after addition of A22.…”
Section: Resultsmentioning
confidence: 99%
“…A22 has been used to reversibly disrupt the localization and function of MreB in C. crescentus and other Gramnegative bacteria (23,32,41,45,52). However, A22 is known to reduce the growth rate of an E. coli mutant that lacks MreB at concentrations of 50 g/ml (212 M) and higher (35), suggesting that A22 inhibits cellular function(s) other than that of MreB.…”
Section: A22mentioning
confidence: 99%
“…To examine how MreB can drive de novo rod shape morphogenesis, we followed a similar strategy except that we used drug treatment to interfere with MreB function. The small molecule 3,4-dichlorobenzyl carbamimidothioate, also known as A22, has been shown to rapidly disrupt MreB localization in vivo and to induce growth-dependent rounding in several Gram-negative bacteria (23,32,41,45,52). Furthermore, genetic and biochemical experiments have shown that MreB is the direct molecular target of A22 and that A22 binds to MreB's ATP-binding pocket, inducing a state with low affinity for polymerization (3,23).…”
mentioning
confidence: 99%
“…5) In addition, A22 has a bacteriostatic effect on E. coli and Shigella flexneri. 5,6) Several groups found some derivatives with similar antibacterial activity against some bacteria through the investigation of structure-activity relationship of A22 derivatives. 7,8) However, all these derivatives thus far were modified on benzyl ring, not isothiourea.…”
mentioning
confidence: 99%